Economic and legal aspects of international environmental agreements: The case of enforcing and stabilising an international CO 2 agreement - Johannes Heister; Ernst Mohr; Wolf Plesmann; Frank Stähler; Peter-Tobias Stoll; Rüdiger Wolfram (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
The protection of the global environment is impeded by multilateral externalities which the international community attempts to bring under control by entering into international agreements. International agreements, however, can suffer from non-compliance and free-riding behaviour by sovereign states and must therefore be enforced and stabilised internationally. This paper describes instruments for the enforcement and stabilisation of an international CO2 agreement and evaluates them in the light of economic and legal theory. Economic instruments build on repetition and use utility transfers, economic sanctions and flexible treaty adjustments. Important legal instruments are reciprocal obligations and cooperation duties, international funding and transfer rules, treaty suspension, retorsions and reprisals, treaty revision, and monitoring. The paper shows that economic and legal instruments are compatible to a considerable extent. It develops proposals for the enforcement and stabilisation of a global CO2 agreement and other multilateral treaties.
Keywords: Q20; K33; 330; International environmental agreements; international cooperation; non-compliance; enforcement; global warming; international law; Umweltabkommen; Klimaveränderung; Kohlendioxid; Gefangenendilemma; Vertrag; Völkerrecht; Internationaler Transfer; Sanktion; Theorie